Energy harvesting performance of BaTiO3/poly(vinylidene fluoride–trifluoroethylene) spin coated nanocomposites. (April 2015) - Nunes-Pereira, J.; Sencadas, V.; Correia, V.; Cardoso, V.F.; Han, Weihua; Rocha, J.G.; Lanceros-Méndez, S.
Abstract: The energy harvesting efficiency of poly(vinylidene fluoride–trifluoroethylene) spin coated films and its nanocomposites with piezoelectric BaTiO3 have been investigated as a function of ceramic filler size and content. It is found that the best energy harvesting performance of ∼0.28 μW is obtained for the nanocomposite samples with 20% filler content of 10 nm size particles and for 5% filler content for the 100 and 500 nm size fillers. For the larger filler average sizes, the power decreases for filler contents above 5% due to increase of the mechanical stiffness of the samples. Due to the similar dielectric characteristics of the samples, the performance is mainly governed by the mechanical response. The obtained power values, easy processing and the low cost and robustness of the polymer, allow the implementation of the material for micro and nanogenerator applications.